subtract 3ab (a-b) from 2ab(a+b) ​

Question

subtract 3ab (a-b) from 2ab(a+b)

in progress 0
Quinn 1 month 2021-08-15T07:42:23+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-15T07:43:26+00:00

    Answer :- -a²b + 5ab²

    Solution

    ⟹ 2ab (a+b) – 3ab (a-b)

    ⟹ 2a²b + 2ab² – 3a²b + 3ab²

    ⟹ 2a²b – 3a²b + 2ab² + 3ab²

    ⟹ -a²b + 5ab²

    Thus, Subtracted

    0
    2021-08-15T07:43:40+00:00

    5ab2-a2b

    I think it may help you

    please mark as a brainliest

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )